Pemanfaatan lumpur limbah industri penyamakan kulit untuk kompos dan pengaruhnya terhadap kandungan krom dalam tanaman uji (jagung dan sawi) - Sri Sutyasmi; Ignatius Sunaryo; Hadi Mustafa; Jaka Susila (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2004)
The aim of this study is to use waste sludge from leather tanning industry for compos and its influence to chromium content in the treatment plant (Zea mays and Brassica chinensis L). In such way it is useful for agriculture and it can prevent the environment pollution. Sludge from leather tanning waste water treatment is around 250 kg per ton hide/skin being processed. If it is not be managed, this kind of sludge will distributes bad smell because of the highly protein content. The nitrogen content within the sludge varies from 2 – 10 %, calcium 10 – 30 %, chromium 0.2 – 3 %, so it is comfortable to use for compos. The activities for making compos were carried out in one of the leather tanning industries in Yogyakarta. Compos was made by following the Windows method with the composition of sludge 45%, rice shell 14.8 %, rice bran 0.2 %, earth 40% and P. Bio 100 ml per kilogram compos mixture. The results of raw sludge of raw sludge analysis before to be used for making compos was N total 2.163%, C organic 44.60%, P. total 0.24%, the available P was 0.012 %, K total 0.54 %, the available K was 0.3 %, C/N ratio was 20.62 and chromium content was 0.39%. the result of compos analysis was N total 0.605%, C organic 82.23%, P total 0.11%, the available P was 0.038%, K total 0.017%, the available K was 0.69%, C/N ratio was 135.98 and chromium content was 0.26%. compos then used for fertilize to Zea mays and Brassica chinensis L and their growth rate were noticed and the chromium content in the Zea mays and Brassica chinensis L was analyzed in the part of roots, stems, leaves and fruits. Based on the noticed and analyzed data could be seen that chromium content in the Zea mays were not be detected; whereas the chromium content in Brassica rugosa were 28.76 g/kg in roots, 30.78 g/kg in stems, 15.30 30.78 g/kg in leaves. It is suggested that this kind of compos don not used for vegetable but for high plants. Keywords : sludge, tanning industry, compos, environment. Tujuan dari penelitian ini adalah memanfaatkan lumpur limbah yang berasal dari UPAL untuk dijadikan kompos dan melihat pengaruhnya terhadap kandungan krom dalam tanaman uji (jagung dan sawi). Dengan demikian dapat bermanfaat untuk petani serta mengatasi masalah lingkungan. Lumpur UPAL industry penyamakan kulit mempunyai volume sekitar 250 kg/ton kulit yang diproses. Lumpur tersebut apabila tidak segera ditangani akan menimbulkan bau busuk karena kandungan proteinnya masih tinggi. Kandungan nitrogen antara 2 – 10%, Calsium 10 – 30%, krom 0,2 – 3 %, sehingga memungkinkan untuk dibuat kompos. Pembuatan kompos dari lumpur dilakukan disalah satu perusahaan penyamakan kulit di daerah Yogyakarta. Metode yang digunakan adalah metode Windrows dengan komposisi lumpur 45%, sekam 14,8%, bekatul 0,2 %, tanah 40% dan P Bio yang digunakan adalah 100 ml/ kg campuran kompos. Hasil uji lumpur sebelum dijadikan kompos N total 2,163 %, C organik 44, 60%, P total 0,24 %, P tersedia 0,012%, K total 0,54 %, K tersedia 0,3% dan C /N ratio 20,62. Sedangkan hasil uji kompos adalah N total 0,605 %, C Organik 82,23%, P total 0,11%, P tersedia 0,038%, K total 0,017 %, K tersedia 0,69% dan C/N ratio 135,98%. Kompos kemudian dipupukkan kedalam tanaman jagung dan sawi dan dilihat pertumbuhannya serta diuji kandungan krom dalam jagung dan sawi mulai dari akar, batang, daun dan buah, kandungan krom dalam jagung tidak terdeteksi sedangkan dalam sawi mulai dari akar, dalam akar 28,7 g/kg, batang 30, 78 g/kg dan pada daun 15,30 g/kg. kompos dari lumpur cocok untuk tanaman tinggi. Kata Kunci : lumpur, industri penyamakan kulit, kompos, lingkungan.